The impact of physical activity on children with adolescent idiopathic scoliosis from Varna, Bulgaria. (30th September 2020) - Marinov, D; Dimitrova, T; Najdenova, D
Abstract: Background: Adolescent idiopathic scoliosis (AIS) is one of the most common chronic conditions in teenagers. There is an increasing amount of evidence suggesting that AIS is associated with low body mass, but the link between the condition and the nutritional status of the adolescents has not been well researched. This ongoing study aims to access the relationship between AIS and all the aspects of the nutritional status in-depth, including factors such as physical activity (PA). Methods: Data is collected from 101 participants with AIS from Varna, Bulgaria using anthropometric measurements, clinical examination to determine the severity of the spinal curvature and questionnaires including a standardized questionnaire for PA of adolescents - PAQ-A. Participants were categorized into 3 groups of AIS severity according to Cobb Angle: mild (10°-19°), moderate (20°-39°) and severe (>40°). Results: Out of 101 participants, 81 had mild, 15 had moderate and 5 had severe scoliotic curvatures. None of the participants reported reduced PA due to impaired or restricted physical functions related to AIS. Only 40% of all subjects with AIS had PAQ-A score over 2.75, which corresponds to the international recommendations of > 60 mins of daily moderate-vigorous PA. There was a strong negative correlation between PAQ-A score and AIS severity (Spearman's Correlation Coefficient = - .433, p < 0.001). The mean PAQ-A score was 2.73 in mild curvatures compared to 1.98 in moderate and severe ones. Subjects with AIS were 4.8 times more likely to have mild severity if they met the PA recommendations (OR = 4, 815 (95%CI, 1.268-18.279)). Those are preliminary results and data will be further compared to a control group. Conclusions: The level of daily PA might have an impact on the severity of AIS. PA recommendations could be given to patients with AIS as a way of secondary prophylaxis against this chronic idiopathic disorder. Key messages: This ongoing study is the first to investigate in-depth the association of all the aspects of nutritional status including PA with the incidence and severity of AIS. PA shows a significant negative correlation with AIS severity. PA recommendations might be a useful addition to the secondary prophylaxis of AIS.